Towards Modern Greek Consciousness - Loukia Droulia (Historical Review, 2005)
This paper deals with the subject of Modern Greek consciousness which can be said epigrammatically to have its starting point in the Provisional Constitution of Greece ratified by the Assembly of Epidaurus in January 1822. For it was then necessary that two crucial questions be answered, namely who were to be considered as citizens of the new state about to be created and what regions it covered. The attempt to find answers to these questions necessarily led to the re-examination of the Greek nation's historical course over the millenia.